Human-friendly robot and bio-inspired robot: new challenge in robotics - Rahman, Md. Mozasser (2016)
The growing need of home automation with the help of robotics system is the driving force of research and development of human-friendly robots. The applications of robot in home automation, agriculture production and medical operations etc. are increasing rapidly. As these types of robots execute tasks in cooperation with human or in close proximity of human, hence need to be designed human-friendly. Researchers proposed many new field of research in Robotics. Cooperative robotics, User friendly robotics and Bio-inspired robotics are new areas of robotics research. Some researcher is trying to make human like robot. Robots that will imitate human characteristics in movement, learning etc. Other researchers are trying to develop robots which will entertain human. Another group is trying to develop robots and/or control systems to work cooperatively. In this presentation it is tried to gather information regarding these fields in brief. The cooperative robots and user friendly robots directly or/and indirectly interact with human. Therefore, human characteristics such as faces, voices, gesture, and movements play an important role in the design and control of such robots. The more human-like the robot appears, the higher the expectations of people interacting with it are. All the aspects of human, physical structure, movements and sensing ability, interaction with environment must be considered to design user friendly and cooperative robots.